Improved models for estimating sporadic-E intensity from GNSS radio occultation measurements - Emmons, Daniel J.; Wu, Dong L.; Swarnalingam, Nimalan; Ali, Ashar F.; Ellis, Joseph A.; Fitch, Kyle E.; Obenberger, Kenneth S. (Frontiers in Astronomy and Space Sciences, 2023)
Several models for estimating sporadic-E intensity from Global Navigation Satellite System (GNSS) radio occultation (RO) observation have previously been developed using a single perturbation or intensity parameter, such as phase-based total electron content (TEC) or the amplitude-based S4 index. Here, we outline two new models that use a combination of phase and amplitude parameters for the L1 and L2 signals. These models show a significant improvement over the baseline models used for comparison. Furthermore, the GNSS-RO parameters are compared with several different ionosonde intensity parameters including the direct foEs & fbEs measurements along with the metallic-ion based foµEs & fbµEs parameters which account for the background E-region density. Interestingly, the phase-based σϕ scintillation index shows the strongest correlation to foEs & fbEs while amplitude-based S4 shows the strongest correlation to foµEs & fbµEs. While the metallic-ion based foµEs & fbµEs parameters are physically ideal for GNSS-RO observations, we show difficulties in practical implementation due to the reliance on a background E-region density estimate using a model such as the International ReferenceIonosphere (IRI). Ultimately, we provide two improved sporadic-E intensity models that can be used for future GNSS-RO based studies along with a recommendation to compare against the ionosonde-based foEs parameter.